Reading Picture Books With Elements of Positive Psychology for Enhancing the Learning of English as a Second Language in Young Children - Hui, Anna N. N.; Chow, Bonnie Wing-Yin; Chan, Eva S. M.; Leung, Man-Tak (Frontiers in Psychology, 2020)
This study aimed to investigate the learning effectiveness of reading picture books with EMPATHICS elements using dialogic reading techniques in enhancing young children’s English language learning and creativity. EMPATHICS is an acronym of Emotion and Empathy, Meaning and Motivation, Perseverance, Agency and Autonomy, Time, Habits of Mind, Intelligences, Character Strengths, and Self Factors (Oxford, 2016). It adopted a quasi-experimental design, and 75 kindergarten children aged from 4 to 5 years old in a cluster group were randomly assigned to the experimental and control groups. Both groups read the same four picture books with their homeroom teachers, including two readers suggested in the curriculum and two picture books with enriched elements for 12 sessions over eight weeks. A doubly multivariate analysis was used to measure the main time and group effects and the interaction effect on the performance of English receptive vocabulary, syntactic complexity and verbal creativity of the two groups across three different times. There were significant differences only in the interactive effect on syntactic complexity. Children in the experimental condition gave responses with more complex syntactic structures. Significant time effects for receptive vocabulary, syntactic complexity, and verbal creativity were observed in all children. Reading enriched English texts better prepares children to creatively and effectively express themselves. This study extends previous research in two ways. First, this study is one of the few studies on the effectiveness of dialogic reading using EMPATHICS-enriched picture books among young language learners. Second, this study investigates the effects of dialogic teaching on English as a second language development in young children. The educational implications will be discussed.